2021
DOI: 10.3390/cancers13071742
|View full text |Cite
|
Sign up to set email alerts
|

Roles of microRNAs in Regulating Cancer Stemness in Head and Neck Cancers

Abstract: Head and neck squamous cell carcinomas (HNSCCs) are epithelial malignancies with 5-year overall survival rates of approximately 40–50%. Emerging evidence indicates that a small population of cells in HNSCC patients, named cancer stem cells (CSCs), play vital roles in the processes of tumor initiation, progression, metastasis, immune evasion, chemo-/radioresistance, and recurrence. The acquisition of stem-like properties of cancer cells further provides cellular plasticity for stress adaptation and contributes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 254 publications
0
6
0
Order By: Relevance
“…Furthermore, it has been shown that miRNA signatures can serve as biomarkers for diagnosis and prognosis, and for predicting a patient’s response to treatment [ 24 , 25 ]. There is also enough evidence to suggest that a significant number of miRNAs are abnormally expressed during HNSCC tumorigenesis and progression, either functioning as OncomiRs or as tumor suppressors [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been shown that miRNA signatures can serve as biomarkers for diagnosis and prognosis, and for predicting a patient’s response to treatment [ 24 , 25 ]. There is also enough evidence to suggest that a significant number of miRNAs are abnormally expressed during HNSCC tumorigenesis and progression, either functioning as OncomiRs or as tumor suppressors [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Epigenetic and post-translational alterations provide additional mechanisms for cancer stem cell reprogramming. Dong et al demonstrated the importance of super enhancers in promoting cancer stem cells ( Dong et al, 2021 ) and there is mounting evidence for the role of microRNAs in cancer stem call regulation ( Bourguignon et al, 2012 ; Barlak et al, 2020 ; Fitriana et al, 2021 ). These necessary metabolic and other perturbations are often driven by interactions with neighboring cells in the tumor microenvironment.…”
Section: Cancer Stem Cell Reprogrammingmentioning
confidence: 99%
“…Inhibition of PDZ-binding kinase (PBK) and p53 activation has the effect of radiosensitization of nasopharyngeal tumors, a process regulated by miR-372. miR-200 is involved in reducing EMT mediated by p53 [ 87 , 88 , 89 ].…”
Section: Micrornas—new Kids On the Hnscc Block—focus On P53 Mediated ...mentioning
confidence: 99%